A continuous flocculants-free electrolytic flotation system for microalgae harvesting. (August 2017) - Luo, Shanshan; Griffith, Richard; Li, Wenkui; Peng, Peng; Cheng, Yanling; Chen, Paul; Addy, Min M.; Liu, Yuhuan; Ruan, Roger
Highlights: A flocculants-free electrolytic flotation harvest system was developed. Highest biomass yield, 23.72 g/h, was achieved at the power consumption of 2.73 kWh/kg. The effluent, free from chemical flocculent, was suitable for reuse in microalgae cultivation. Abstract: High harvesting cost and reusing of post-harvest water are the major challenges in commercial production of microalgae. In this work, a flocculants-free electrolytic flotation harvest process was investigated. The electrode design and materials were evaluated in terms of harvesting efficiency. Stainless steel as the cathode and carbon as the anode were selected based on the harvesting efficiency data and non-sacrificial feature for construction of a pilot scale harvesting system. In the pilot scale experiments, 23.72 g/h biomass yield was achieved at the power consumption of 2.73 kWh/kg. With the advantages of no chemical flocculent contamination and relatively low energy requirement, this continuous system is promising for food or feed applications.